TIPE-TIPE STOMATA TUMBUHAN MYRTACEAE DI LINGKUNGAN KAMPUS FKIP ULM SEBAGAI BOOKLET BAHAN AJAR PENDAMPING MATA KULIAH ANATOMI TUMBUHAN - Aulia, Oriza Mety; Amintarti, Sri; Rezeki, Amalia (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
The campus environment of FKIP ULM Banjarmasin consists of various plant families, one of which is the Myrtaceae family. Differences in plant families and species can affect the type of plant stomata. The type of stomata can be used to add data about phylogenetic systematics in plants. This study aims to describe the types of stomata of Mytaceae plants in the Campus Environment of FKIP ULM Banjarmasin. The research started from September 2022 to December 2022. The Myrtaceae leaf sampling technique was carried out using cruise methods. Stomata-type data collection method using a light microscope. The research data obtained were analyzed by descriptive qualitative. The results of the study found 2 types of stomata from 7 species of Myrtaceae plants namely: anomocytic/ranunculaceous stomata type found in Syzygium malaccense and Syzygium aqueum white fruit and parasitic/rubiaceous stomata type found in red fruit Syzygium aqueum, Syzygium jambos, Syzygium oleana, Psidium guajava, and Syzygium polyanthum.